PENGARUH OPTIMISME TERHADAP ADVERSITY QUOTIENT PADA MAHASISWA YANG BEKERJA DI UNIVERSITAS MUHAMMADIYAH GORONTALO - Syamsul Abdul Aziz; Anik Indarwati; Rahmawaty Parman (Elsia: Jurnal Psikologi Manusia, 2024)
The Effect of Optimism on Adversity Quotient in Working Students at the Universitas Muhammadiyah Gorontalo. Supervised by Anik Indarwati, as the chair and Rahmawaty Parman, as a member. This study used a quantitative approach to determine the effect of optimism on the adversary ratio of working students at the Universitas Muhammadiyah Gorontalo. The sampling technique used was simple random sampling, with a research sample of 70 working students. The data collection technique used optimism and adversity quotient questionnaires, and the research method used simple linear regression analysis. This study’s results showed a significant effect of Optimism on the Adversity Quotient, with the t count being greater than or equal to the t table (3.149 ≥ 1.670) and a significance value of 0.002 ≤ 0.05. This indicated that there was a significant influence between Optimism and Adversity Quotient. The influence given was 12.7%, and the remaining was influenced by variables other than optimism.